Comparative health systems a global perspective - Johnson, James A. 1954-; Stoskopf, Carleen H. (Carleen Harriet) 1953-; Shi, Leiyu (Jones Bartlett Learning LCC, 2018)
Global health policy, administration, and practice continue to evolve while countries throughout the world seek to balance their economic and health goals through health system reform, improvement, and modification. The Second Edition of Comparative Health Systems: A Global Perspective addresses emerging events, advances, reforms, and challenges in the delivery of health care around the world. Part I offers introduces foundational concepts of health care delivery systems including health and disease; and policy and economics. In Part II, the health systems of 19 unique countries are each examined in their own chapter including France, United Kingdom, Canada, Brazil, Peru, Nigeria, Australia, China, Japan, Russia, and Israel. These chapters carefully explore the country's geography and culture, the history of its health system, followed by a detailed evaluation of cost, quality, access and innovation. Ideal for courses in health administration, public health, nursing and other allied health professions, this innovative text challenges readers to reflect deeply about how health care is organized and delivered. Key Features: " Includes two new chapters that explore innovation and sustainability; and the role and contributions of non-governmental organizations " Examines challenges and opportunities such as disaster and conflict, the changing U.S. health system, and a new chapter on small country innovations " Offers new perspectives in evidence-based approaches to health system improvement; systems thinking at the policy level; integrated information management; macro and micro innovation, and systems sustainability.